OBSTRÜKTİF UYKU APNE SENDROMU’NDA NCPAP TEDAVİSİNE UYUMA GÖRSEL AĞIRLIKLI EĞİTİMİN KATKISI - ÖZTÜRK, Levent; PELİN, Zerrin and KAYNAK, Derya and SALBACAK, Lokman and ÖZGÜR, Canip and MUTLU, Ayser and KAYNAK, Hakan (Cerrahpaşa Medical Journal, 2019)
Background and Design.- Nasally applied continuous positive airway pressure (NCPAP) is a highly effective, nonsurgical form of treatment for obstructive sleep apnea. The NCPAP apparatus is bulky, cosmetically unappealing and associated with a number of adverse reactions. Several factors such as severity of sleep apnea, excessive daytime sleepiness, previous surgery as well as NCPAP apparatus may have a role in acceptance and compliance of NCPAP therapy. Various desensitization techniques have been devised to help patients better tolerate and accept treatment. In an attempt to identify effect of video assisted education on NCPAP acceptance, we evaluated 196 patients with obstructive sleep apnea referred to our laboratory for NCPAP trials. Patients were divided into two groups. Before undergoing first night NCPAP trial, the first group (n=84, male: 73%, female: 27%) was informed about their diagnosis, complications of the disease and mechanism of NCPAP treatment by an interview. The second group (n=112, male: 72%, female: 28%) was informed in the same manner and they watched video film to visualize sleep apnea and its consequences and reversal of symptoms by NCPAP therapy. Subjects who accepted and started NCPAP therapy compared with the subjects who did not accept NCPAP in both groups. A probability value less than 0,05 was considered statistically significant. Results.- In the first group (mean age ± SD = 51±10), 15 of the 84 subjects rejected NCPAP treatment. Acceptance rate of NCPAP in the first group was 82%. In the second group (mean age±SD= 52 ± 9), only 7 of the 112 subjects refused NCPAP treatment. Acceptance rate was 93% for this group. There was no difference between two groups in terms of age, sex and RDI. Conclusion.- The findings indicate that the patients who undergo video assisted education about their diagnosis and treatment accept NCPAP therapy more easily.